Laporan Kasus: Hipertensi Disertai Obesitas - Syamsir, Feryansyah Akhbar; Makmum, Armanto (Yayasan Citra Cendekia Celebes, 2024)
Hypertension is a non-communicable disease that can cause death without causing symptoms or is asymptomatic, so this disease is often known as the